Marketing Mix (4P) to Increase Sales Volume at Rumah Hijab Nayyura MSMEs - JATMIKO, NOVI SATRIA; Nada’a Utami, Jihan (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
Marketing Mix Research (4P) to Increase Sales Volume of MSMEs Rumah Hijab Nayyura is to determine the influence of exogenous variables (Product, Price, Place, and Promotion) on endogenous variables (Sales Volume). The samples taken were resellers from Rumah Hijab Nayyura, as many as 50 people. The results showed that Product (X1) had a positive and significant effect on sales volume of 0.581, Price had a positive but not significant influence on sales volume of 0.032, Place had a positive but not significant influence on sales volume of 0.181, and Promotion had a positive but not significant influence on sales volume of 0.141.